(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we recall some basic concepts, properties of the spaces and some types of iteration approaches. Also, we give algorithm - fixed point iteration scheme and examples. Finally, we obtain the solution of nonlinear equations of the form using Mann iteration.